Mechanism for establishing and maintaining the reproductive hierarchy in a eusocial mammal, the Damaraland mole-rat. (December 2019) - Kelley, John B.; Carter, Sara N.; Goldman, Bruce D.; Goldman, Sharry; Freeman, David A.
Abstract : Eusociality is exhibited by colonial-living organisms where only a few individuals within a colony reproduce; the remaining members are nonbreeders and support reproduction of the breeders. Damaraland mole-rats, Fukomys damarensis, are one of two mammal species considered eusocial. Colonies include a breeding pair and their offspring. Unusual aspects of reproductive behaviour include the observation that both sexes display all components of mating even after long-term absence of gonadal hormones. Mating does not occur between siblings or offspring and parents, but nonbreeders from one colony will mate with individuals from other colonies. However, following 5 weeks of separation from each other, siblings will exhibit mutual sexual behaviour. Thus, familiarity through frequent proximity, rather than genetic identity, mediates inbreeding avoidance. One caveat is that breeding pairs maintain a mating relationship for years, although they obviously become familiar with each other. Among Damaraland mole-rats that are familiar with each other, two types of relationships can form, a mating relationship or a 'sibling-like' relationship marked by inbreeding avoidance. The factors determining the relationship between pairs of Damaraland mole-rats remain undefined. This experiment tested the hypothesis that the behaviour during the initial meeting of a pair of Damaraland mole-rats determines which relationship forms, i.e. mating versus 'sibling-like'. The initial pairing occurred either with unrestrained physical contact (allowing for mating behaviours) or with the two animals separated from each other by a mesh barrier (no mating could occur). This initial pairing was followed by daily 20 min pairings with the barrier in place for 2 weeks and then a final pairing without any restraint. Results indicate that the nature of the interaction within the first 20 min of meeting determines the long-term sexual relationship between pairs of Damaraland mole-rats. The results suggest a mechanistic basis for establishment and maintenance of the reproductive hierarchy in this eusocial species. Highlights: We examined factors contributing to the strict reproductive hierarchy in mole-rats. Mole rats that mated at their first encounter maintained a mating relationship. Mole-rats familiarized 2 weeks before mating did not develop a mating relationship. Mole-rats may thus form breeding relationships during dispersal from natal colonies. Consequently, offspring may fail to exhibit mating behaviours within their colony.